The Panstereorama: City Models in the Balloon Era. Issue Volume 70:Issues 1(2018) (2nd January 2018) - Ellis, Patrick
Abstract: The nineteenth-century 'panstereorama' was an urban relief model placed on display as a public spectacle. In this article, I consider first two affiliated forms that help to explain the genre, namely panorama paintings and plans-reliefs . I then go on to consider urban regional practices of city modelling in London and Paris before examining in detail panstereoramas representing Paris and New York. It is argued that this form of model urban cartography served as proxy for the view obtained from the increasingly popular balloon trip and that it accordingly provided virtual travel to, and a map of, the cities depicted.